ADVANCED-PLATELET RICH FIBRIN - A NEW ACQUISITION IN JAW OSTEONECROSIS TREATMENT - Daniel Vlad; Ion Bordeianu; Adrian Creangă (Romanian Society of Oral Rehabilitation, 2018)
Introduction. Osteonecrosis of the jaw represents an adverse effect of a classes of drugs with both anti-osteoclastic properties and antiangiogenic properties [1], the causal association of this type of medication with osteonecrosis of the jaw was established more than a decade ago. Aim of the study. The aim of the present study is to analyze the evolution of osteonecrosis in patients whose alveolar bone was protected postextractional with A-PRF (advanced - platlet rich fibrin). Material and methods. In this study, 14 patients were enrolled in bisphosphonate therapy (osteonecrosis stage 0) requiring dental extractions. We analyzed the particular general health informations of each patient and performed the necessary dental extractions, followed by the application of A-PRF and the wound's suture. A-PRF was obtained by centrifugation of the venous blood (14 minutes at 1500 rpm) using a Choukroun model centrifuge. Patients were monitored at 7 and 30 days. Results and Discussion. We have noticed that the greatest risk of triggering bisphosphonate-induced osteonecrosis is associated with the presence of a history of neoplasia, the type of bisphosphonates used (zoledronic acid), the duration of treatment greater than 3 years and the route of intravenous administration. The 7-day post-operative evolution was uncomplicated in 85.7% of cases, epithelialization of the alveolar socket being recorded in 100% of cases at the 30-day control. Conclusions. The use of A-PRF is an effective method for prevention of the onset of osteonecrosis of the jaw in patients who have been treated with bisphosphonates. The advantage of this method is the high mechanical stability of A-PRF and the stimulation of bone regeneration.